Coupled Antigen and BLIMP1 Asymmetric Division With a Large Segregation Between Daughter Cells Recapitulates the Temporal Transition From Memory B Cells to Plasma Cells and a DZ-to-LZ Ratio in the Germinal Center - Merino Tejero, Elena; Lashgari, Danial; García-Valiente, Rodrigo; He, Jiaojiao; Robert, Philippe A.; Meyer-Hermann, Michael; Guikema, Jeroen E. J.; Hoefsloot, Huub; van Kampen, Antoine H. C. (Frontiers in Immunology, 2021)
Memory B cells and antibody-secreting plasma cells are generated within germinal centers during affinity maturation in which B-cell proliferation, selection, differentiation, and self-renewal play important roles. The mechanisms behind memory B cell and plasma cell differentiation in germinal centers are not well understood. However, it has been suggested that cell fate is (partially) determined by asymmetric cell division, which involves the unequal distribution of cellular components to both daughter cells. To investigate what level and/or probability of asymmetric segregation of several fate determinant molecules, such as the antigen and transcription factors (BCL6, IRF4, BLIMP1) recapitulates the temporal switch and transzone migration rates in the germinal center, we implemented a multiscale model that combines a core gene regulatory network for plasma cell differentiation with a model describing the cellular interactions and dynamics in the germinal center. Our simulations show that BLIMP1 driven plasma cell differentiation together with coupled asymmetric division of antigen and BLIMP1 with a large segregation between the daughter cells results in a germinal center transzone migration rate and a temporal switch from memory B cells to plasma cells that have been observed in experiments.